Student teachers’ views on content knowledge of environmental issues in biological and geoscience subject matters - Yli-Panula, Eija; Banos-Gonzalez, Isabel; Jeronen, Eila; Matikainen, Eila (Modestum Ltd, 2026)
Subject content knowledge (SCK) and pedagogical content knowledge (PCK) are key components of teacher
competence that affect teaching and students’ learning and thinking about the future. In this study, SCK and PCK
were analyzed from Finnish and Spanish (n = 360) primary school student teachers’ (PSTs) answers using a
questionnaire that included environmental problems and teaching sustainability. The answers were analyzed
with theoretically guided deductive and inductive content analyses. The PSTs considered it important to teach
factual, conceptual, methodological and metacognitive knowledge and skills for solving local, regional and global
environmental problems. Critical and evaluative knowledge also appeared, but in rather few answers. The results
are discussed regarding the meaning of SCK and PCK and a powerful knowledge of science disciplines, such as
biology and the geosciences.